Pengembangan Instrumen Penilaian Pembelajaran Matematika Berbasis Higher Order Thinking Skills (HOTS) Menggunakan Quizizz Pada Materi Penyajian Data di Kelas IV SD Alam Lukulo Kebumen - Khotimah, Widia Khusnul; Maryanto, Maryanto (IAINU Kebumen, 2024)
This research aims to develop a valid and practical HOTS-based learning assessment instrument using the quizizz application. This research method uses the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research involved 4th grade students of SD Alam Lukulo which amounted to 6 people as subjects. The research instruments consisted of a material expert validation questionnaire, a linguist validation questionnaire, and an educator response questionnaire as well as student interview results. The data generated from data collection using instruments is then analyzed for validity and practicality. The results of the research obtained are: (1) the average material validation score of 50 which is included in the achievement level of interval ≥81.5 – 100 at a percentage of 100% with very valid criteria, the average language validation score of 23 which is included in the achievement level of interval ≥81.5 – 100 at a percentage of 92% with very valid criteria; (2) the average response score of educators is 51 which is included in the level of achievement of the interval 86 - 100 at the percentage of 92.75 with very practical criteria; (3) the results of student interviews are HOTS-based assessment instrument products using quizizz are very interesting and increase student enthusiasm. so the HOTS-based assessment instrument using quizizz meets valid and practical criteria.